Effects of cell volume regulating osmolytes on glycerol-3-phosphate binding to triosephosphate isomerase - Gulotta, Miriam (2007)
During cell volume regulation, intracellular concentration changes occur in both inorganic and organic osmolytes in order to balance the extracellular osmotic stress and maintain cell volume homeostasis. Generally, salt and urea increase the K(m)s of enzymes and TMAO counteracts these effects by decreasing K(m)s. The hypothesis to account for these effects is that urea and salt shift the native state ensemble of the enzyme toward conformers that are substrate binding incompetent (BI), while TMAO shifts the ensemble toward binding competent (BC) species. K(m)s are often complex assemblies of rate constants involving several elementary steps in catalysis, so to better understand osmolyte effects we have focused on a single elementary event, substrate binding. We test the conformational shift hypothesis by evaluating the effects of salt, urea and TMAO on the mechanism of binding glycerol-3-phosphate, a substrate analogue, to yeast triosephosphate isomerase. Temperature-jump kinetic measurements promote a mechanism consistent with osmolyte-induced shifts in the [BI]/[BC] ratio of enzyme conformers. Importantly, salt significantly affects the binding constant through its effect on the activity coefficients of substrate, enzyme and enzyme-substrate complex, and it is likely that TMAO and urea affect activity coefficients as well. Results indicate that the conformational shift hypothesis alone doesn’t account for the effects of osmolytes on K(m)s.